The Effects of Self-Compassion and Social Responsibility on Promoting Prosocial Behavior Among University Students - Paga, Belina Amelia; Amir, Yulmaida (unprimdn.ac.id, 2025)
Prosocial behavior, which aims to benefit others, has become part of Indonesian culture. This study aims to analyze the effects of self-compassion and social responsibility on this prosocial behavior in university students. The study participants totaled 119 students, using a simple random sampling technique. The research data were analyzed with multiple linear regression tests. The results of data analysis showed a p-value = 0.000 (p < 0.05), which means a significant relationship exists between self-compassion, social responsibility, and prosocial behavior.